Comparison of long-term outcome in patients with calcified stenosis treated with intravascular lithotripsy or with modified balloon angioplasty: a propensity score-adjusted study - Leick, Jürgen; Rheude, Tobias; Denne, Michael; Cassese, Salvatore; Kastrati, Adnan; Hauptmann, Felix; Gehrig, Thomas; Kuna, Constantin; Lindner, Michael; Lauterbach, Michael; Werner, Nikos (Frontiers in Cardiovascular Medicine, 2023)
Background The aim of this two-center, all-comers registry was to compare the effectiveness and safety of intravascular lithotripsy (IVL) to that of modified balloon angioplasty (MB). MB angioplasty using a cutting or scoring balloon is commonly used in patients with calcified coronary arteries. IVL is a new technology for lesion preparation. This is the first study to compare MB with IVL. Methods The cohort included all patients treated by MB angioplasty or IVL between 2019 and 2021. The primary endpoint was strategy success (<20% residual stenosis). The secondary endpoint was long-term safety outcomes [cardiac death, acute myocardial infarction (AMI), target lesion failure/revascularization (TVR)]. Quantitative coronary angiography (QCA) was performed in all patients. Primary and secondary endpoints were compared using inverse probability of treatment weighting (IPTW) for treatment effect estimation. Results A total of n = 86 patients were treated by IVL and n = 92 patients by MB angioplasty. The primary endpoint was reached in 152 patients (85.4%). Patients in the IVL group had less residual stenosis (5.8% vs. 22.8%; p = 0.001) in QCA. Weighted multivariable regression analysis revealed that IVL had a significant positive effect on reaching the primary endpoint of strategy success [odds ratio (OR) 24.58; 95% confidence interval (95% CI) 7.40–101.86; p = 0.001]. In addition, severe calcification was shown to result in a lower probability of achieving the primary endpoint (OR 0.08; 95% CI 0.02–0.24; p = 0.001). During the follow-up period (450 days) there was no difference in cardiovascular mortality rate [IVL (n = 5) 2.8% vs. MB (n = 3) 1.7%; p = 0.129]. Patients with unstable angina at the time of the index procedure had the highest probability of cardiovascular death [hazard ratio (HR) 7.136; 95% CI 1.248–40.802; p = 0.027]. No differences were found in long-term rates of AMI (IVL 1.7% vs. MB 2.8%; p = 0.399; IVL HR 2.73; 95% CI 0.4–17.0; p = 0.281) or TVR (IVL 5.6% vs. MB 9%; p = 0.186; IVL HR 0.78; 95% CI 0.277–2.166; p = 0.626). Conclusion IVL leads to a significantly better angiographic intervention outcome compared to MB angioplasty in our cohort. During long-term follow-up, no differences in cardiovascular mortality, rate of acute myocardial infarction, or target lesion failure/revascularization were observed.